5.14.8 Problems 701 to 800

Table 5.863: First order ode non-linear in derivative

#

ODE

Mathematica

Maple

10474

\[ {}y {y^{\prime }}^{2}-{\mathrm e}^{2 x} = 0 \]

10475

\[ {}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

10476

\[ {}y {y^{\prime }}^{2}+2 x y^{\prime }-9 y = 0 \]

10477

\[ {}y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0 \]

10478

\[ {}y {y^{\prime }}^{2}-4 x y^{\prime }+y = 0 \]

10479

\[ {}y {y^{\prime }}^{2}-4 a^{2} x y^{\prime }+a^{2} y = 0 \]

10480

\[ {}y {y^{\prime }}^{2}+a x y^{\prime }+b y = 0 \]

10481

\[ {}y {y^{\prime }}^{2}+x^{3} y^{\prime }-x^{2} y = 0 \]

10482

\[ {}y {y^{\prime }}^{2}-\left (y-x \right ) y^{\prime }-x = 0 \]

10483

\[ {}\left (x +y\right ) {y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

10484

\[ {}\left (y-2 x \right ) {y^{\prime }}^{2}-2 \left (x -1\right ) y^{\prime }+y-2 = 0 \]

10485

\[ {}2 y {y^{\prime }}^{2}-\left (4 x -5\right ) y^{\prime }+2 y = 0 \]

10486

\[ {}4 y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

10487

\[ {}9 y {y^{\prime }}^{2}+4 x^{3} y^{\prime }-4 x^{2} y = 0 \]

10488

\[ {}a y {y^{\prime }}^{2}+\left (2 x -b \right ) y^{\prime }-y = 0 \]

10489

\[ {}\left (a y+b \right ) \left (1+{y^{\prime }}^{2}\right )-c = 0 \]

10490

\[ {}\left (b_{2} y+a_{2} x +c_{2} \right ) {y^{\prime }}^{2}+\left (a_{1} x +b_{1} y+c_{1} \right ) y^{\prime }+a_{0} x +b_{0} y+c_{0} = 0 \]

10491

\[ {}\left (a y-x^{2}\right ) {y^{\prime }}^{2}+2 x y {y^{\prime }}^{2}-y^{2} = 0 \]

10492

\[ {}x y {y^{\prime }}^{2}+\left (x^{2}+y^{2}\right ) y^{\prime }+x y = 0 \]

10493

\[ {}x y {y^{\prime }}^{2}+\left (x^{22}-y^{2}+a \right ) y^{\prime }-x y = 0 \]

10494

\[ {}\left (2 x y-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+2 x y-y^{2} = 0 \]

10495

\[ {}\left (2 x y-x^{2}\right ) {y^{\prime }}^{2}-6 x y y^{\prime }-y^{2}+2 x y = 0 \]

10496

\[ {}a x y {y^{\prime }}^{2}-\left (y^{2} a +b \,x^{2}+c \right ) y^{\prime }+b x y = 0 \]

10497

\[ {}y^{2} {y^{\prime }}^{2}-a^{2}+y^{2} = 0 \]

10498

\[ {}y^{2} {y^{\prime }}^{2}-6 x^{3} y^{\prime }+4 x^{2} y = 0 \]

10499

\[ {}y^{2} {y^{\prime }}^{2}-4 a y y^{\prime }+4 a^{2}-4 a x +y^{2} = 0 \]

10500

\[ {}y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }+y^{2} a +b x +c = 0 \]

10501

\[ {}y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+a -x^{2}+2 y^{2} = 0 \]

10502

\[ {}y^{2} {y^{\prime }}^{2}+2 a x y y^{\prime }+\left (a -1\right ) b +a \,x^{2}+\left (1-a \right ) y^{2} = 0 \]

10503

\[ {}\left (y^{2}-a^{2}\right ) {y^{\prime }}^{2}+y^{2} = 0 \]

10504

\[ {}\left (y^{2}-2 a x +a^{2}\right ) {y^{\prime }}^{2}+2 a y y^{\prime }+y^{2} = 0 \]

10505

\[ {}\left (y^{2}-a^{2} x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+\left (-a^{2}+1\right ) x^{2} = 0 \]

10506

\[ {}\left (\left (1-a \right ) x^{2}+y^{2}\right ) {y^{\prime }}^{2}+2 a x y y^{\prime }+x^{2}+\left (1-a \right ) y^{2} = 0 \]

10507

\[ {}\left (y-x \right )^{2} \left (1+{y^{\prime }}^{2}\right )-a^{2} \left (1+y^{\prime }\right )^{2} = 0 \]

10508

\[ {}3 y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-x^{2}+4 y^{2} = 0 \]

10509

\[ {}\left (3 y-2\right ) {y^{\prime }}^{2}-4+4 y = 0 \]

10510

\[ {}\left (-a^{2}+1\right ) y^{2} {y^{\prime }}^{2}-2 a^{2} x y y^{\prime }+y^{2}-a^{2} x^{2} = 0 \]

10511

\[ {}\left (a -b \right ) y^{2} {y^{\prime }}^{2}-2 b x y y^{\prime }+y^{2} a -b \,x^{2}-a b = 0 \]

10512

\[ {}\left (y^{2} a +b x +c \right ) {y^{\prime }}^{2}-b y y^{\prime }+d y^{2} = 0 \]

10513

\[ {}\left (a y-b x \right )^{2} \left (a^{2} {y^{\prime }}^{2}+b^{2}\right )-c^{2} \left (a y^{\prime }+b \right )^{2} = 0 \]

10514

\[ {}\left (\operatorname {b2} y+\operatorname {a2} x +\operatorname {c2} \right )^{2} {y^{\prime }}^{2}+\left (\operatorname {a1} x +\operatorname {b1} y+\operatorname {c1} \right ) y^{\prime }+\operatorname {b0} y+\operatorname {a0} +\operatorname {c0} = 0 \]

10515

\[ {}x y^{2} {y^{\prime }}^{2}-\left (y^{3}+x^{3}-a \right ) y^{\prime }+x^{2} y = 0 \]

10516

\[ {}x y^{2} {y^{\prime }}^{2}-2 y^{3} y^{\prime }+2 x y^{2}-x^{3} = 0 \]

10517

\[ {}x^{2} \left (x y^{2}-1\right ) {y^{\prime }}^{2}+2 x^{2} y^{2} \left (y-x \right ) y^{\prime }-y^{2} \left (x^{2} y-1\right ) = 0 \]

10518

\[ {}\left (y^{4}-a^{2} x^{2}\right ) {y^{\prime }}^{2}+2 a^{2} x y y^{\prime }+y^{2} \left (y^{2}-a^{2}\right ) = 0 \]

10519

\[ {}\left (y^{4}+x^{2} y^{2}-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }-y^{2} = 0 \]

10520

\[ {}9 y^{4} \left (x^{2}-1\right ) {y^{\prime }}^{2}-6 x y^{5} y^{\prime }-4 x^{2} = 0 \]

10521

\[ {}x^{2} \left (x^{2} y^{4}-1\right ) {y^{\prime }}^{2}+2 x^{3} y^{3} \left (y^{2}-x^{2}\right ) y^{\prime }-y^{2} \left (y^{2} x^{4}-1\right ) = 0 \]

10522

\[ {}\left (a^{2} \sqrt {x^{2}+y^{2}}-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+a^{2} \sqrt {x^{2}+y^{2}}-y^{2} = 0 \]

10523

\[ {}\left (a \left (x^{2}+y^{2}\right )^{{3}/{2}}-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+a \left (x^{2}+y^{2}\right )^{{3}/{2}}-y^{2} = 0 \]

10524

\[ {}{y^{\prime }}^{2} \sin \left (y\right )+2 x y^{\prime } \cos \left (y\right )^{3}-\sin \left (y\right ) \cos \left (y\right )^{4} = 0 \]

10525

\[ {}{y^{\prime }}^{2} \left (a \cos \left (y\right )+b \right )-c \cos \left (y\right )+d = 0 \]

10526

\[ {}f \left (x^{2}+y^{2}\right ) \left (1+{y^{\prime }}^{2}\right )-\left (x y^{\prime }-y\right )^{2} = 0 \]

10527

\[ {}\left (x^{2}+y^{2}\right ) f \left (\frac {x}{\sqrt {x^{2}+y^{2}}}\right ) \left (1+{y^{\prime }}^{2}\right )-\left (x y^{\prime }-y\right )^{2} = 0 \]

10528

\[ {}\left (x^{2}+y^{2}\right ) f \left (\frac {y}{\sqrt {x^{2}+y^{2}}}\right ) \left (1+{y^{\prime }}^{2}\right )-\left (x y^{\prime }-y\right )^{2} = 0 \]

10529

\[ {}{y^{\prime }}^{3}-\left (y-a \right )^{2} \left (y-b \right )^{2} = 0 \]

10530

\[ {}{y^{\prime }}^{3}-f \left (x \right ) \left (y^{2} a +b y+c \right )^{2} = 0 \]

10531

\[ {}{y^{\prime }}^{3}+y^{\prime }-y = 0 \]

10532

\[ {}{y^{\prime }}^{3}+x y^{\prime }-y = 0 \]

10533

\[ {}{y^{\prime }}^{3}-\left (x +5\right ) y^{\prime }+y = 0 \]

10534

\[ {}{y^{\prime }}^{3}-a x y^{\prime }+x^{3} = 0 \]

10535

\[ {}{y^{\prime }}^{3}-2 y y^{\prime }+y^{2} = 0 \]

10536

\[ {}{y^{\prime }}^{2}-a x y y^{\prime }+2 y^{2} a = 0 \]

10537

\[ {}{y^{\prime }}^{3}-\left (y^{2}+x y+x^{2}\right ) {y^{\prime }}^{2}+\left (x y^{3}+x^{2} y^{2}+x^{3} y\right ) y^{\prime }-x^{3} y^{3} = 0 \]

10538

\[ {}{y^{\prime }}^{3}-y^{4} y^{\prime } x -y^{5} = 0 \]

10539

\[ {}{y^{\prime }}^{3}+a {y^{\prime }}^{2}+b y+a b x = 0 \]

10540

\[ {}{y^{\prime }}^{3}+x {y^{\prime }}^{2}-y = 0 \]

10541

\[ {}{y^{\prime }}^{3}-y {y^{\prime }}^{2}+y^{2} = 0 \]

10542

\[ {}{y^{\prime }}^{2}-\left (x^{2}+x y^{2}+y^{4}\right ) {y^{\prime }}^{2}+\left (x y^{6}+x^{2} y^{4}+y^{2} x^{3}\right ) y^{\prime }-x^{3} y^{6} = 0 \]

10543

\[ {}a {y^{\prime }}^{3}+b {y^{\prime }}^{2}+c y^{\prime }-y-d = 0 \]

10544

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+a = 0 \]

10545

\[ {}4 x {y^{\prime }}^{3}-6 y {y^{\prime }}^{2}-x +3 y = 0 \]

10546

\[ {}8 x {y^{\prime }}^{3}-12 y {y^{\prime }}^{2}+9 y = 0 \]

10547

\[ {}\left (-a^{2}+x^{2}\right ) {y^{\prime }}^{3}+b x \left (-a^{2}+x^{2}\right ) {y^{\prime }}^{2}+y^{\prime }+b x = 0 \]

10548

\[ {}x^{3} {y^{\prime }}^{3}-3 y {y^{\prime }}^{2} x^{2}+\left (x^{6}+3 x y^{2}\right ) y^{\prime }-y^{3}-2 x^{5} y = 0 \]

10549

\[ {}2 \left (x y^{\prime }+y\right )^{3}-y y^{\prime } = 0 \]

10550

\[ {}{y^{\prime }}^{3} \sin \left (x \right )-\left (y \sin \left (x \right )-\cos \left (x \right )^{2}\right ) {y^{\prime }}^{2}-\left (y \cos \left (x \right )^{2}+\sin \left (x \right )\right ) y^{\prime }+y \sin \left (x \right ) = 0 \]

10551

\[ {}2 {y^{\prime }}^{3} y-y {y^{\prime }}^{2}+2 x y^{\prime }-x = 0 \]

10552

\[ {}y^{2} {y^{\prime }}^{3}+2 x y^{\prime }-y = 0 \]

10553

\[ {}16 y^{2} {y^{\prime }}^{3}+2 x y^{\prime }-y = 0 \]

10554

\[ {}x y^{2} {y^{\prime }}^{3}-y^{3} {y^{\prime }}^{2}+x \left (x^{2}+1\right ) y^{\prime }-x^{2} y = 0 \]

10555

\[ {}x^{7} y^{2} {y^{\prime }}^{3}-\left (3 x^{6} y^{3}-1\right ) {y^{\prime }}^{2}+3 x^{5} y^{4} y^{\prime }-x^{4} y^{5} = 0 \]

10556

\[ {}{y^{\prime }}^{4}-\left (y-a \right )^{3} \left (y-b \right )^{2} = 0 \]

10557

\[ {}{y^{\prime }}^{4}+3 \left (x -1\right ) {y^{\prime }}^{2}-3 \left (2 y-1\right ) y^{\prime }+3 x = 0 \]

10558

\[ {}{y^{\prime }}^{4}-4 y \left (x y^{\prime }-2 y\right )^{2} = 0 \]

10559

\[ {}{y^{\prime }}^{6}-\left (y-a \right )^{4} \left (y-b \right )^{3} = 0 \]

10560

\[ {}x^{2} \left (1+{y^{\prime }}^{2}\right )^{3}-a^{2} = 0 \]

10561

\[ {}{y^{\prime }}^{r}-a y^{s}-b \,x^{\frac {r s}{r -s}} = 0 \]

10562

\[ {}{y^{\prime }}^{n}-f \left (x \right )^{n} \left (y-a \right )^{n +1} \left (y-b \right )^{n -1} = 0 \]

10563

\[ {}{y^{\prime }}^{n}-f \left (x \right ) g \left (y\right ) = 0 \]

10564

\[ {}a {y^{\prime }}^{m}+b {y^{\prime }}^{n}-y = 0 \]

10565

\[ {}x^{n -1} {y^{\prime }}^{n}-n x y^{\prime }+y = 0 \]

10566

\[ {}\sqrt {1+{y^{\prime }}^{2}}+x y^{\prime }-y = 0 \]

10567

\[ {}\sqrt {1+{y^{\prime }}^{2}}+x {y^{\prime }}^{2}+y = 0 \]

10568

\[ {}x \left (\sqrt {1+{y^{\prime }}^{2}}+y^{\prime }\right )-y = 0 \]

10569

\[ {}a x \sqrt {1+{y^{\prime }}^{2}}+x y^{\prime }-y = 0 \]

10570

\[ {}y \sqrt {1+{y^{\prime }}^{2}}-a y y^{\prime }-a x = 0 \]

10571

\[ {}a y \sqrt {1+{y^{\prime }}^{2}}-2 x y y^{\prime }+y^{2}-x^{2} = 0 \]

10572

\[ {}f \left (x^{2}+y^{2}\right ) \sqrt {1+{y^{\prime }}^{2}}-x y^{\prime }+y = 0 \]

10573

\[ {}a \left (1+{y^{\prime }}^{3}\right )^{{1}/{3}}+b x y^{\prime }-y = 0 \]